2011
DOI: 10.1007/s11139-010-9244-3
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Askey–Wilson function and bispectrality

Abstract: For every positive integer d, we define a meromorphic function F d (n; z), where n, z ∈ C d , which is a natural extension of the multivariable Askey-Wilson polynomials of Gasper and Rahman (Theory and Applications of Special Functions, Dev. Math., vol. 13, pp. 209-219, Springer, New York, 2005). It is defined as a product of very-well-poised 8 φ 7 series and we show that it is a common eigenfunction of two commutative algebras A z and A n of difference operators acting on z and n, with eigenvalues depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the context of q−special functions and the q−Virasoro algebra, a similar extension has been considered too [67,108]. In view of these, it is clear that an extension of the bispectral problem (2.16), (2.17) for N > 1 can be considered similarly, see for instance [109]. These works may establish a relation between the q−Onsager algebra and an algebraic structure extending the q−Virasoro algebra.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of q−special functions and the q−Virasoro algebra, a similar extension has been considered too [67,108]. In view of these, it is clear that an extension of the bispectral problem (2.16), (2.17) for N > 1 can be considered similarly, see for instance [109]. These works may establish a relation between the q−Onsager algebra and an algebraic structure extending the q−Virasoro algebra.…”
Section: Perspectivesmentioning
confidence: 99%
“…Van Diejen and E. Koelink for sending us reprints [17] and [110], respectively. P.B thanks E. Koelink for detailed explanations on the work [110], as well as P. Iliev for communications and sending us a reprint of [109]. We thank P. Terwilliger for important comments on the manuscript and sending us the preprint [43].…”
mentioning
confidence: 99%
“…where h n (x, α, β, N; q) are the q-Hahn polynomials (15). These polynomials are orthogonal with respect to the same measure as the Gasper-Rahman q-Hahn polynomials H (α) n (y) given by (25).…”
Section: Another Family Of Multivariate Q-hahn Polynomialsmentioning
confidence: 99%
“…where h n (x, α, β, N; q) and p n (x, α, β; q) are the q-Hahn and q-Jacobi polynomials defined in (15) and (34). We now set x 1 = (u − v)/2, x 2 = (u + v)/2 as well as t = q u+1 , and we consider the limit of (51) as v → ∞.…”
Section: The D = 3 Case: One-variable Q-racah Polynomialsmentioning
confidence: 99%
“…We will recover the orthogonality relations with respect to (1.3) below. Iliev [15] (see also [12]) showed that the multivariate Askey-Wilson polynomials are eigenfunctions of d commuting difference operators. Furthermore, the multivariate Askey-Wilson polynomials are also eigenfunctions of commuting difference equations in m, i.e.…”
Section: Introductionmentioning
confidence: 99%